Hiring Costs and Temporary Work Agencies. An explication of regional disparities across Spanish provinces - García-del-Barrio, Pedro (2013)
The Temporary Work Agencies (TWA) industry experienced continuous growth throughout the 90s, and now represents around 15% of temporary hiring in Spain. More interestingly, are markable regional disparity in this sector exists across Spanish provinces. By developing a simple theoretical model and using panel data methodology, this article examines the Spanish caseand suggests that the costs of recruiting, training and screening could explain a large part of the regional disparity. This result is supported by the empirical fact that the TWA firms have greater success in markets with low unemployment rates, where the average duration of unemploymen tis longer, and in provinces with higher concentrations of urban population, respectively.